2018
DOI: 10.1007/978-3-030-00931-1_50
|View full text |Cite
|
Sign up to set email alerts
|

Joint Prediction and Classification of Brain Image Evolution Trajectories from Baseline Brain Image with Application to Early Dementia

Abstract: Despite the large body of existing neuroimaging-based studies on brain dementia, in particular mild cognitive impairment (MCI), modeling and predicting the early dynamics of dementia onset and development in healthy brains is somewhat overlooked in the literature. The majority of computer-aided diagnosis tools developed for classifying healthy and demented brains mainly rely on either using single timepoint or longitudinal neuroimaging data. Longitudinal brain imaging data offer a larger time window to better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…For instance, [3] predicted the multishape trajectory of the baby brain using neonatal MRI data. Similarly, [4] and [5] used MR images to predict brain image evolution trajectories for early dementia detection. Although pioneering, such works mainly focused on Euclidean structured data (i.e, images), which is a flat representation of the brain and does not reflect the connectivity patterns existing among brain regions encoded in brain networks (i.e, connectomes).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, [3] predicted the multishape trajectory of the baby brain using neonatal MRI data. Similarly, [4] and [5] used MR images to predict brain image evolution trajectories for early dementia detection. Although pioneering, such works mainly focused on Euclidean structured data (i.e, images), which is a flat representation of the brain and does not reflect the connectivity patterns existing among brain regions encoded in brain networks (i.e, connectomes).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have developed shape-based and image-based prediction frameworks using morphological features derived from brain MRI scans to foresee the brain evolution trajectory [5,6]. For instance, [6] used a representative shape selection method to predict longitudinal development of cortical surfaces and white matter fibers assuming that similar shapes at baseline timepoint will have similar developmental trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, [6] used a representative shape selection method to predict longitudinal development of cortical surfaces and white matter fibers assuming that similar shapes at baseline timepoint will have similar developmental trajectories. Such an assumption has been also adopted in a landmark study [5], demonstrating the reliability of exploring similarities between baseline training and testing samples for predicting the evolution of brain MR image trajectory in patients diagnosed with mild cognitive impairment. Although these works proposed successful predictive frameworks for image-based brain evolution trajectory prediction and classification, these were solely restricted to investigating the brain as a surface or a 3D image.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereby, it is vital to undertake an early diagnosis of brain diseases [2], especially for neurodegenerative diseases such as dementia which was found to be irreversible if discovered at a late stage [3]. In this context, recent landmark studies [4,5] have suggested using the robust predictive abilities of machine learning to predict the time-dependent (i.e., longitudinal) evolution of both the healthy and the disordered brain. However, such works only focus on predicting the brain when modeled as an image or a surface, thereby overlooking a wide spectrum of brain dysconnectivity disorders that can be pinned down by modeling the brain as a graph (also called connectome) [6], where the connectivity weight between pairs of anatomical regions of interest (ROIs) becomes the feature of interest.…”
Section: Introductionmentioning
confidence: 99%